2008
DOI: 10.1021/ma801478c
|View full text |Cite
|
Sign up to set email alerts
|

Sorption, Dilation, and Partial Molar Volumes of Carbon Dioxide and Ethane in Cross-Linked Poly(ethylene oxide)

Abstract: Experimental gas solubility and sorptive dilation data are reported for carbon dioxide and ethane in a cross-linked poly(ethylene oxide) rubber prepared by photopolymerization of poly(ethlyene glycol)diacrylate. Five different operating temperatures (253 e T (K) e 308) were considered, with a maximum gas pressure of 2.16 MPa (21.3 atm). The importance of taking sorptive dilation into account in the determination of gas solubility in polymers by the pressure-decay method was demonstrated. Sorption isotherms in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
46
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 27 publications
(52 citation statements)
references
References 77 publications
(222 reference statements)
5
46
1
Order By: Relevance
“…This hydrogel is inert and therefore suitable for various applications such as diapers, female hygiene products, wound dressings, controlled release drug systems, and solid electrolytes for batteries. [ 6,12,[40][41][42][43] Riberio and Freeman [ 13 ] studied the dilation and sorption processes of carbon dioxide/ethane (CO 2 a concentration range of CO 2 in the gas phase from 10 to 70 mol%. In another study, Claudio and Riberio [ 6,12 ] estimated the PMV of CO 2 and C 2 H 6 in the XLPEO at different temperatures using the binary dilation-sorption data of CO 2 /XLPEO and ethane/XLPEO systems.…”
Section: Co 2 /Ethane/cross-linked Poly(ethylene Oxide) Ternary Systemmentioning
confidence: 99%
See 3 more Smart Citations
“…This hydrogel is inert and therefore suitable for various applications such as diapers, female hygiene products, wound dressings, controlled release drug systems, and solid electrolytes for batteries. [ 6,12,[40][41][42][43] Riberio and Freeman [ 13 ] studied the dilation and sorption processes of carbon dioxide/ethane (CO 2 a concentration range of CO 2 in the gas phase from 10 to 70 mol%. In another study, Claudio and Riberio [ 6,12 ] estimated the PMV of CO 2 and C 2 H 6 in the XLPEO at different temperatures using the binary dilation-sorption data of CO 2 /XLPEO and ethane/XLPEO systems.…”
Section: Co 2 /Ethane/cross-linked Poly(ethylene Oxide) Ternary Systemmentioning
confidence: 99%
“…[ 6,12,[40][41][42][43] Riberio and Freeman [ 13 ] studied the dilation and sorption processes of carbon dioxide/ethane (CO 2 a concentration range of CO 2 in the gas phase from 10 to 70 mol%. In another study, Claudio and Riberio [ 6,12 ] estimated the PMV of CO 2 and C 2 H 6 in the XLPEO at different temperatures using the binary dilation-sorption data of CO 2 /XLPEO and ethane/XLPEO systems. The ternary CO 2 (1)/ C 2 H 6 (2)/XLPEO(3) dilation data of Riberio and Freeman [ 13 ] at two different temperatures (i.e., 25 and 35 °C) were used to validate the proposed methodology for the calculation of the PMVs of penetrating molecules in multicomponent systems.…”
Section: Co 2 /Ethane/cross-linked Poly(ethylene Oxide) Ternary Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…Solubility data for CO 2 and a few other gases at 35 °C are available for some materials,8, 9, 14–16 whereas systematic studies at other temperatures were reported by Lin and Freeman19 and Kelman et al18 However, all these data were obtained without considering the effect of polymer dilation, which can lead to errors in the reported solubility data, since experimental methods for measuring gas solubility in polymers are sensitive to the volume of the polymer sample 20, 21. It was only very recently that both sorption and dilation of two gases (carbon dioxide and ethane) in a XLPEO (prepared from PEGDA) were experimentally measured 22. These data confirmed that to obtain more accurate gas solubility values in XLPEOs by the pressure‐decay method, the changes in the volume of the polymer sample due to gas sorption and thermal expansion should be taken into account.…”
Section: Introductionmentioning
confidence: 99%